A new look at glutamate and ischemia: NMDA agonist improves long-term functional outcome in a rat model of stroke. (November 2011) - Dhawan, Jasbeer; Benveniste, Helene; Luo, Zhongchi; Nawrocky, Marta; Smith, S David; Biegon, Anat
Ischemic stroke triggers a massive, although transient, glutamate efflux and excessive activation of NMDA receptors (NMDARs), possibly leading to neuronal death. However, multiple clinical trials with NMDA antagonists failed to improve, or even worsened, stroke outcome. Recent findings of a persistent post-stroke decline in NMDAR density, which plays a pivotal role in plasticity and memory formation, suggest that NMDAR stimulation, rather than inhibition, may prove beneficial in the subacute period after stroke.Aim: This study aims to examine the effect of the NMDAR partial agonistD -cycloserine (DCS) on long-term structural, functional and behavioral outcomes in rats subjected to transient middle cerebral artery occlusion, an animal model of ischemic stroke.Materials & methods: Rats (n = 36) that were subjected to 90 min of middle cerebral artery occlusion were given a single injection of DCS (10 mg/kg) or vehicle (phosphate-buffered saline) 24 h after occlusion and followed up for 30 days. MRI (structural and functional) was used to measure infarction, atrophy and cortical activation due to electrical forepaw stimulation. Memory function was assessed on days 7, 21 and 30 postocclusion using the novel object recognition test. A total of 20 nonischemic controls were included for comparison.Results: DCS treatment resulted in significant improvement of somatosensory and cognitive function relative to vehicle treatment. By day 30, cognitive performance of the DCS-treated animals was indistinguishable from nonischemic controls, while vehicle-treated animals demonstrated a stable memory deficit. DCS had no significant effect on infarction or atrophy.Conclusion: These results support a beneficial role for NMDAR stimulation during the recovery period after stroke, most likely due to enhanced neuroplasticity rather than neuroprotection.